Trabalho no setor de viagens e turismo em Foz do Iguaçu (1970-2018) - Schumann , Ivanete Terezinha (2021)
The world of work in tourism is composed of historical links with the agenda of the working class claims for rights to have leisure and better work conditions. Tourism organization became the subject of the public sector that designed it, implementing labor rights and conditions for the access of a large number of people to tourist places. With this, the travel and tourism sector is formed, based on concepts of work organization, systemic organization, a powerful business market and tourism economy. In the projection of the production system and consumption, or in supply and demand, service companies have assumed the mission of organizing productive management and jobs. The places are transformed into tourist sites, with structures, companies and occupations that become places where people travel. This market constituted the characteristic activities of tourism, as part of the capitalist system development, imbricated in institutionalization processes and public and private bodies structuring, for work organization, labor relations and the business and employment market. Institutionalization develops planning, projects, regulations, legislations. Tourism becomes synonymous with employment, it becomes a goal and justification for the implementation of tourism projects, with the intensification of identification of attractive potential options, all over the world. Nature and culture are the attractions that stand out, as well as the places where they are located, they become tourism destinations. Foz do Iguaçu, located in the west of Paraná, is one of these places, of exuberant nature, with the Iguaçu Falls, and of cultural diversity formed by the historical context of constitution, settlement and development of the municipality. A place of trinational border and Mercosur's strategic location of economic interest where the flow of people and business potential aroused interest from people from several countries. The city was transformed into a tourist destination by actions of groups that operate in the tourism economy network, controlling businesses and jobs. Jobs in tourism pay little and demand a lot. They acquire contradictory characteristics to the economic results announced by entrepreneurs, of being a sector with excellent profitability levels and of constant increase in GDP. Therefore, it is necessary to put on the agenda the working condition reality of those who are the tourism productive force and to debate the economic bias.